2016
DOI: 10.1016/j.jinteco.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Relational contracts and supplier turnover in the global economy

Abstract: Headquarters and their specialized component suppliers have a vital interest in establishing long-term collaborations. When formal contracts are not enforceable, such efficiency enhancing cooperation's can be established via informal agreements, but relational contracts have been largely ignored in the literature on the international organization of value chains. In this paper, we develop a dynamic property rights model of global sourcing. A domestic headquarter collaborates with a foreign input supplier and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Given these risks and uncertainties, it is unsurprising that complex, but (still) incomplete contracts govern the actual trade interactions. In addressing these complex contracts and their dynamic nature, Defever et al (2016) and Kukharskyy (2016) have shown that only sufficiently patient firms may establish efficient long-term supplier collaborations. Findings by Araujo et al (2016); Aeberhardt et al (2014) and Rauch and Watson (2003) point to relationships being developed slowly, starting with small test orders until a relationship is established, reflecting reciprocity considerations.…”
Section: Related Literaturementioning
confidence: 99%
“…Given these risks and uncertainties, it is unsurprising that complex, but (still) incomplete contracts govern the actual trade interactions. In addressing these complex contracts and their dynamic nature, Defever et al (2016) and Kukharskyy (2016) have shown that only sufficiently patient firms may establish efficient long-term supplier collaborations. Findings by Araujo et al (2016); Aeberhardt et al (2014) and Rauch and Watson (2003) point to relationships being developed slowly, starting with small test orders until a relationship is established, reflecting reciprocity considerations.…”
Section: Related Literaturementioning
confidence: 99%
“…In part VII, I use the duration of trade relationships (Defever, Fischer, & Suedekum, ) instead of correlation of trade flows over time. Long trade duration ( h ) is defined as trade spells at HS6 product ( p ) and country of destination ( c )/dispatch ( d ) that are active for more than 3 years.…”
Section: Resultsmentioning
confidence: 99%
“…Long trade duration (h) is defined as trade spells at HS6 product (p) and country of destination (c)/dispatch (d) that are active for more than 3 years. 12 Further the weighted average of specific product in total value of firm export/import is used to define the variable of contractual exporter/importer: 11 Defever, Fischer, and Suedekum (2016) T A B L E 9 (Continued) | 2593…”
Section: Robustness Checksmentioning
confidence: 99%
“…Bernanke et al (2005), pointing to the Mundell Fleming trilemma, recall that the independence of EMEs monetary policy is limited if they wish to maintain a stable exchange rate. Furthermore, Defever et al (2016), stressing the important interconnectedness of global economies through trade and financial markets, advocates that monetary policy has to consider the interest setting abroad because of exchange rate and export effects. They claim that moderate foreign growth and low foreign interest rates had prevented from early return to monetary normalization.…”
Section: On Output Development and The Currency Valuementioning
confidence: 99%